Aspectos agronômicos e produtividade de soja submetida a manejo de irrigação - Nunes, Antônia Clemilda (2015)
The Irrigated agriculture is responsible for the consumption a substantial fraction of all the fresh water used in Brazil and is evident, every day, this feature is becoming increasingly scarce. Following this context, appropriate methods of irrigation management that establish strategies for water saving, keeping reasonable levels of productivity that are fundamental to maintaining sustainable food production. This study has had like objective to evaluate the effects of the application of irrigation blades with deficit in soybean. The research was conducted in an experimental area of the Federal University of Tocantins on the Palmas College - TO. The experimental lineation was in random blocks with four repetitions, and the treatments were being putted on a plan of subdivided portions. The portions consisted in irrigation blades which induced the plants to drought in the growing season, reproductive and during all the cycle, reference to crop potential evapotranspiration (ETpc), in the following way: 25V25R - the culture was subjected to severe stress water during all of cycle, being irrigated with 25% of ETpc; 50V50R - the culture was subjected to drought during the whole cycle, receiving 50% of ETpc; 100V100R - the plants did not undergo to drought, being irrigated with 100% ETpc; 25V100R - the plants received drought, 25% of ETpc, during all the growing season, starting differentiation in V1; 50V100R: the plants received 50% of ETpc during the growing season, differentiation begins in V1; 100V25R - the plants were irrigated with 25% of ETpc in the reproductive stage, begins to differentiation R1 and 100V50R - 50% of ETpc, starting differentiation in R1. The subplots matched at two soybean the M9144RR RR and the TMG1288RR RR, which were sown on the day 06/20/2014. The variables were evaluated: days to flowering, days to maturity, plant height, first pod height, number of pods per plant, stem diameter, leaf area, productivity. In relation to grains, were evaluated polar and equatorial diameters, relationship between the equatorial and polar diameter, 1000 grain weight and oil and protein contents thereof. Were evaluated too the yield of oil and protein and efficiency of water use in the production of grain, oil and protein. The irrigation managements had meaningly influence the agronomic characteristics of the cultivars. Productivity and variables related to grain quality were influenced significantly for treatments (T) and cultivars (C), as well as the interaction treatments x cultivars (T x C). As for oil and protein content, was observed in both cultivars, in the treatments that happened increase in protein content, there was a decrease in oil content, but the yield as oil as protein, followed the same trend of the grain productivity, and the best treatments were the 100V100R and 50V100R, should be noted that moderate drought in the growing season occurred in 50V100R treatment yielded productivity values higher than the 100V100R and in this treatement the culture didn’t surfer a stress water indicating that the irrigation management in soybeans with a deficit in this period results in higher levels of productivity and in bigger efficiency of water use by the crop. The moderate drought in the growing season contributed to the oil and protein yield values presented similar values to those found in treatment in that culture did not suffer drought during whole cycle. Both cultivars showed different responses under drought. The cultivar TMG1288RR, presented more resistant to dry period, but the M9144RR on favorable conditions to the expression of its genetic potential, in this case, treatment with drought of 50% of ETpc in the growing season, showed bigger productivity.